Los medios audiovisuales de la ciudad de Loja y su incidencia en la juventud lojana de las formas de expresión musical nativas - Labanda Ordoñez, Lorena del Cisne (2015)
The lack of native broadcasting of artistic expression of music in the media of the city of Loja, Loja makes youth largely unknown musical roots. This work was conducted in the city of Loja, whose objectives were oriented to an analysis of the real situation of the audiovisual media of Loja city, and identify and contribute to the spread of programs and projects that the native musical expression of our city, to the community and determine the effectiveness of communication currently used with their audiences, analyze the participation and involvement of young people in programs, projects and proposals of the media to spread our music; recognize the concerns of young people; that allow the media positioning and recognition in the environment; develop a proposal to strengthen our music; in pursuit of that same expectation it is generated and the spread timely and thus have informed the lojana youth and who know about the musical culture of our city. In order to obtain the information required for the fulfillment of the objectives several surveys the citizens of the city were made and UV managers. Television and TV Ecotel., That information is analyzed it and proceeded to statistics, corresponding interpretation. The population or universe that was taken into account for the realization of this research were 214 thousand inhabitants of Canton Loja, the sample was represented by each lojano citizens both urban and rural areas. With the information gathered it was reached the following conclusions based on results such as determining that 87% do not know anything about music native programs that are transmitted on local television channels and 12% yes and 1% a nothing thereby we intend to develop a program to try to solve the problem of this research is the lack of native music programs in our city. Keywords: channel, communication, Loja, music, programs.